Information and Inventory in Distribution Channels - Iyer, Ganesh; Narasimhan, Chakravarthi; Niraj, Rakesh (Management Science, 2007)
We examine the trade-offs between demand information and inventory in a distribution channel. While better demand information has a positive direct effect for the manufacturer in improving the efficiency of holding inventory in a channel, it can also have the strategic effect of increasing retail prices and limiting the extraction of retail profits. Having inventory in the channel can help the manufacturer to manage retail pricing behavior while better extracting retail surplus. Thus, even if the information system is perfectly reliable, the manufacturer might not always want to institute an information-enabled channel over a channel with inventory. We show this first in a channel with a single retailer, where the channel with perfect information is preferred over the channel with inventory only if the marginal cost of production is sufficiently high. We also analyze a channel with an imperfectly reliable information system and find that if the manufacturer were to choose the precision of the demand information system, it might not prefer perfect information, even if such information was costless to acquire. In a channel with competing retailers, the channel with perfect information is preferred when retail competition is sufficiently intense. Thus, the presence of inventory can play a role in managing competition among retailers and in helping the manufacturers to appropriate surplus especially when retailers are sufficiently differentiated.